DNSWeight: Quantifying Country-Wise Importance of Domain Name System - Deliang Chang; Shanshan Hao; Zhou Li; Baojun Liu; Xing Li (IEEE Access, 2021)
DNS (Domain Name System) is one fundamental Internet infrastructure related to most network activities. As a feasible tool to govern the Internet, DNS’s stability and interoperability will be impacted by the countries’ policies or actions along the path. Especially now that many countries have stricter control over the Internet and even sometimes “unplug” it. But there was no study to quantify the countries’ impact systematically. To fill this research gap, we present DNSWeight. This new data-driven approach utilizes a large-scale DNS dataset and BGP (Border Gateway Protocol) routing information to calculate the country-importance score so that a country’s impact on DNS can be gauged. By applying DNSWeight on large-scale DNS and BGP datasets jointly, our study shows the importance among different countries is divided. A handful of countries show dominant significance to the current DNS ecosystem. Some countries with a history of Internet shutdowns are too influential to be ignored if they choose to break themselves from the Internet. We also examine the impact of IPv6 (IP Version 6) and reveal the “loop” phenomenon that occurs in some DNS queries. In conjunction with our findings, some discussion and suggestions are given. In summary, our study shows that DNS reliability needs to be reconsidered at the country’s level.